An Analysis of Students’ Perception toward Reading Comprehension Skill Before and After Joining English club - Viny Bellyana; Ririn Ovilia (Journal of English Language Teaching, 2023)
This study aimed to analyze the students’ perception toward reading comprehension skills before and after joining English club. The study was a descriptive qualitative research. The participants in this study were 10 students who had joined the English club for one year. The data were collected through an interview, which included 12 questions. The findings showed that students had a positive perception toward reading comprehension skills after joining the English club. There were changes in the students' reading comprehension skills between before and after joining the English club. It can be concluded that the students agreed that their reading comprehension skills improved after joining the English club.